Probiotic administration among free-living older adults: a double blinded, randomized, placebo-controlled clinical trial. Issue 1 (December 2015) - Östlund-Lagerström, Lina; Kihlgren, Annica; Repsilber, Dirk; Björkstén, Bengt; Brummer, Robert; Schoultz, Ida
Abstract Background Diseases of the digestive system have been found to contribute to a higher symptom burden in older adults. Thus, therapeutic strategies able to treat gastrointestinal discomfort might impact the overall health status and help older adults to increase their overall health status and optimal functionality. Objective The aim of this double-blinded, randomized, placebo-controlled clinical trial was to evaluate the effect of the probiotic strainLactobacillus reuteri on digestive health and wellbeing in older adults. Methods The study enrolled general older adults (>65 years). After eligibility screening qualified subjects (n  = 290) participated in a 2-arm study design, with each arm consisting of 12 weeks of intervention of either active or placebo product. Primary outcome measure was set to changes in gastrointestinal symptoms and secondary outcome measures were changes in level of wellbeing, anxiety and stress. Follow up was performed at 8 and 12 weeks. Results No persistent significant effects were observed on the primary or secondary outcome parameters of the study. A modest effect was observed in the probiotic arm, were levels of stress decreased at week 8 and 12. Similarly, we found that subjects suffering from indigestion and abdominal pain, respectively, showed a significant decrease of anxiety at week 8 after probiotic treatment, but not at week 12. Conclusion The RCT failed to show any improvement in digestive health after daily intake of a probiotic supplement containingL. reuteri . Neither was any significant improvement in wellbeing, stress or anxiety observed. Even though the RCT had a negative outcome, the study highlights issues important to take into consideration when designing trials among older adults. Trial registration Clinicaltrials.gov/NCT01837940 .